Matrix Analysis to Additive Schwarz Methods (Journal of Computational Mathematics, 2021)
Matrix analysis on additive Schwarz methods as preconditioners is given in this paper. Both cases of with and without coarse mesh are considered. It is pointed out that an advantage of matrix analysis is to obtain more exact upper bound. Our numerical tests access the estimations.